Estrategias competitivas de la gestión del marketing en la empresa “Qualite” de la ciudad de Riobamba y la participación en el mercado a través del incremento de ventas, periodo 2017 - León Molina, Juan Carlos (2019)
The purpose of this research is to identify the correlation between marketing management strategies and market participation in the micro-sector dedicated to providing laundry services in the city of Riobamba, with the aim of proposing strategies that improve the management of the marketing; For this purpose, the company "Qualite" of the city mentioned above was considered as a case study. A survey was developed for the clients and employees and an interview was held with the manager of the company indicated above, with which the perspectives of the client, workers and investor were determined with greater objectivity. Knowing the results of the research, it is concluded that applying market penetration and consolidation strategies are a key factor from the marketing point of view, however, it is not determined in the increase of productivity and business profitability, but is complemented with the development of new services, new markets, innovation, specialization and adequate dissemination of the services it offers, which today are a powerful tool to interact in a highly competitive market and are crucial to increase customers, improve productivity and consequently obtain higher profitability The strategies proposed in this paper constitute an important support for the economic growth of the microenterprises that provide the laundry service.